2008
DOI: 10.1093/ndt/gfn581
|View full text |Cite
|
Sign up to set email alerts
|

Spatial QRS-T angle in peritoneal dialysis patients: association with carotid artery atherosclerosis, coronary artery calcification and troponin T

Abstract: QRS-T is high in PD patients and is mainly associated with coronary artery calcium burden, atherosclerosis and troponin T elevation. The possible clinical importance of the higher QRS-T in PD patients remains to be confirmed in further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 31 publications
3
14
0
Order By: Relevance
“…Our present study demonstrates that spatial QRS- T angle , T elev , and T az are significantly higher among patients with end-stage renal disease despite patients were treated by hemodialysis or staying on continuous ambulatory peritoneal dialysis. As we previously demonstrated, QRS- T angle is markedly higher in CAPD patients than in control ones [10]. The present analysis demonstrates that other vectorocardiographic parameters are also higher in patients with end-stage renal disease.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our present study demonstrates that spatial QRS- T angle , T elev , and T az are significantly higher among patients with end-stage renal disease despite patients were treated by hemodialysis or staying on continuous ambulatory peritoneal dialysis. As we previously demonstrated, QRS- T angle is markedly higher in CAPD patients than in control ones [10]. The present analysis demonstrates that other vectorocardiographic parameters are also higher in patients with end-stage renal disease.…”
Section: Discussionsupporting
confidence: 80%
“…According to previously described formulas [10, 11], the following parameters concerning T vector was analyzed off-line from the averaged QRST complexes via customized software (Cardioperfect, version 1.1, CardioControl NV, Rijswijk, The Netherlands, Figure 2):…”
Section: Methodsmentioning
confidence: 99%
“…41 FQRSTA is a very powerful predictor of cardiovascular events (e.g., myocardial ischemia), 42 sudden cardiac death, [13][14][15][16][17]43 appropriate ICD therapy, 44,45 all-cause mortality, 15,[33][34][35][36][37] increased cardiac-related hospitalizations, 17,35 reduced left ventricular function, [34][35][36]46 especially in patients with postinfarction, [13][14][15][16][17] acute myocardial infarction with LVEF ࣘ40%, 47 the elderly, 12 chronic dialysis, [18][19][20] heart failure with preserved ejection fraction, 17 and ischemic stroke 48 considered stronger than any of the classical cardiovascular risk factors. 16,17 Risk factors leading to an elevation in FQRSTA were related to coronary artery disease, dialysis, poor-controlled hypertension, 49,50 pulmonary arterial hypertension, 51 left/right ventricular hypertrophy, 51-54 dilated left ventricle, 55 lower LVEF, 56 DM, 57, 58 smoking, [57][58][59] and female gender.…”
Section: Dm and Fqrstamentioning
confidence: 99%
“…Recent reports showed that the maximal magnitude of frontal QRS-T angle (FQRSTA) was significantly associated with the prognosis of elderly patients, 12 myocardial infarction, [13][14][15][16][17] heart failure, 17 and chronic dialysis. [18][19][20] There was no report about the influence of DM on the virtual planar QRS vector, T vector, and FQRSTA, derived from a Holter monitor. In this study, we randomly enrolled several patients with and without type 2 DM (NDM) in order to exploit the influence of DM on planar QRS and T vector virtually derived from Holter.…”
mentioning
confidence: 99%
“…The non-invasive identification of individuals at risk for cardiovascular events is a significant clinical dilemma, and there are many ongoing studies searching for new riskstratification indices. 1 Calcification of different tissues is an endstage event in the inflammation process. Vascular calcification is detected either in the tunica intima or in the tunica media.…”
mentioning
confidence: 99%